ANALISIS POTENSI STRUKTUR EKONOMI UNGGULAN DAN DAYA SAING SUB SEKTOR PERTANIAN DI KOTA BATU TAHUN 2011-2015 - Mochamad Sulistyo Kurniawan; Sudarti Sudarti; Zainal Arifin (Program Studi Ekonomi Pembangunan, 2017)
One of the stages to develop the strategic area is to identify the superior sub-sectors and competitiveness owned. The agricultural sector is the dominant potential in Batu City. To identify the superior sub sectors and agricultural competitiveness, LQ, DLQ and Shift Share analysis were performed. The data used in the analysis process is GRDP, production value and growth rate. Preferred sub-sectors are selected based on LQ and DLQ calculations with value> 1, to see the developing potential. For competitiveness use Sheft Share analysis with positive Cij value. Based on the result of research analysis, got the superior sub-sector result of strategic area of Batu City economic growth is on Horticulture and Agricultural Services sub sector. And for the competitiveness of agricultural sub-sector of Batu City has positive Cij value which means have competitive advantage in agriculture sector. Keywords: Leading Potency, Agricultural Sector, Location quotient, Shift Share Analysis